Use of Recycled Aggregate as Alkali Activator to Enhance Strength Development in High-Volume Blast-Furnace Slag Concrete - Han, Dongyeop; Kim, Jun-Ho; Han, Mincheol; Yi, Seong-Tae (KSCE journal of civil engineering, 2020)
The aim of the research is to achieve the strength development performance of high-volume slag concrete or zero-cement concrete with 0.45 of W/B by incorporating of recycled aggregates as a cost-effective alkali activator. Based on the blast-furnace slag (BFS) based cement, like an alkali activated slag (AAS), recycled aggregates were replaced by natural aggregates and were used as an alkali activator for BFS. For compressive strength improvement in concrete, different replacement ratios of ordinary Portland cement ranged from zero to 50%, recycled fine aggregates (RFA) and recycled coarse aggregates (RCA) ranged from zero to 100% were varied. The test results indicated that recycled aggregates could be used as an alkali activator for BFS, and they were also able to help achieve about 90% of compressive strength of the concrete with natural aggregate depending on its optimum proportion with BFS.